General and Specific Interfaces: Experiences with a Multimedia Platform - Bargeron, David; Grudin, Jonathan; Gupta, Anoop (2001)
Tradeoffs have always existed between a consistent, widely-used interface and interfaces optimized for specific purposes. However, the balance may be shifting toward a focus on specialized interfaces due to increased capabilities of software and rising expectations of users. We illustrate these effects through the description of a multimedia annotation system deployed in a series of laboratory and field studies. Laboratory studies identified more generic problems and guided general improvements. Field studies invariably identified context-specific requirements that presented challenges for a general interface. These studies have implications for the designers and users of multimedia systems and suggest a broader trend away from applications and toward platforms.